Histórias em quadrinhos na cultura digital: construindo um framework didático baseado na pedagogia dos multiletramentos - RODRIGUES, Raiane Assunção (Universidade Federal do Oeste do Pará, 2024)
In contemporary times, everyday practices have been surrendering to different electronic devices capable of helping to carry out tasks and activities varied, covering scopes from work to leisure. through computers personal computers and mobile devices (cell phones, tablets, notebooks), ordinary people have been mobilizing a wide range of languages that give them access to new ways of materializing thoughts, experiences, feelings, and visions of world. In this scenario, not only new expressive modalities emerge, but also remodeling and remediation of preexisting languages. In between the most relevant are those that relate to the stories in comics (HQs). This work aims to investigate the similarities between the language of comics and the pedagogy of multiliteracies, to formulate an educational framework made up of didactic actions that can be replicated and adapted in formal and non-formal educational contexts. This is qualitative bibliographic exploratory research, which operates according to the principles of Design Science Research (DSR). We understand that the construction of an educational framework can represent a strategic resource for educators in search of a didactic-pedagogical basis to develop literacy actions focused on the language of comics. Finally, as a result, the research presents a brief table describing learning actions focused on comics and aligned with the knowledge processes of multiliteracy pedagogy.